Gestos e produções vocais: a fluência multimodal em aquisição da linguagem - Silva, Paula Michely Soares da (2014)
Among the various studies in language acquisition, one of the researches that has been growing is the one that proposes to observe the multimodal aspect of language; such works have enriched the research in language acquisition in a meaningful way. It is from this perspective that McNeill (1985) proposes that gesture and speech are in a same matrix of meaning, in other words, it is considered the gestures and vocal productions as components of multimodality in language acquisition. Thus, this study aims to examine the presence of gestures, especially the gesticulation simultaneously with vocal productions, composing a third element, the multimodal fluency in the language acquisition process. For this, we take as the theoretical apparatus, the proposal of McNeill (1985) in respect to the relationship between gesture and speech. Kendon (1982), in turn, performs a significant role in the study of gestures to classify gestural movements from a "continuous", called "continuous of Kendon". It is precisely through this "continuous" that the referred author considers gesticulations as the gestures that accompany the flow of speech involving arms, neck and head movements, body posture and legs, has marks of speech community and marks of the individual style of each one. With regard to the infant speech output, we rely upon Barros (2012) and proposed a typology for the vocal productions of the child. For the emergence of fluency we take as bases the authors Scarpa (1995) and Merlo (2006). According to Scarpa (1995) "the fluency is present in adjacent pairs, stereotyped statements, family members, frozen, often in immediate situation in expressions that exhibit greater stability." (p. 7). Therefore, we seek to understand the relationship between the emergence of gestures and vocal productions composing multimodal fluency into the process of language acquisition. For this work we will analyze a mother-baby aged 6 to 24 months of a child's life, recorded in naturalistic situation in the house of the dyad fortnightly.